Crab Mentality in Higher Education: A Phenomenological Exploration of Its Implications for Human Resource Development - Mega Suteki; Diah Harmawati (Dinasti Publisher, 2025)
Crab mentality, often described as a tendency to obstruct or undermine the success of others, poses a significant challenge to collaboration and human resource development (HRD) within higher education institutions. This study employed a qualitative phenomenological approach to explore how academics experience crab mentality, how they interpret and cope with it, and what implications it holds for HRD strategies. Data were collected from 15 purposively selected participants, including lecturers, administrative staff, and unit heads, at university X in Papua, Indonesia, through in-depth interviews, participant observation, and document analysis. The findings reveal that crab mentality manifests through passive-aggressive behaviors, lack of collegial support, resistance to innovation, and the downplaying of others’ achievements. Participants described feelings of isolation, mistrust, and alienation, which undermined their motivation and willingness to engage in collaborative projects. Organizational factors such as hierarchical structures, individual-based promotion systems, and competitive reforms aimed at achieving world-class university status further reinforced the prevalence of crab mentality. Despite these challenges, participants demonstrated coping strategies including endurance, selective collaboration, and seeking support from trusted peers. The study highlights that crab mentality directly contradicts the goals of HRD by weakening professional development, obstructing leadership cultivation, and reducing organizational learning capacity. To mitigate these effects, strategic HRD interventions are recommended, including team-based reward systems, transformational leadership development, structured mentoring programs, and transparent HR policies. These interventions are critical for fostering an academic culture that values collaboration, inclusivity, and innovation, thereby strengthening both institutional cohesion and global competitiveness.